Psychology of the Facelift Patient - Sarcu, David; Adamson, Peter (Facial Plastic Surgery, 2017)
This paper presents an extensive literature review of the psychology of facelift patients as it has evolved over the past 50 years. Earlier studies revealed significant levels of pre and perioperative depression. Facelift patients generally exhibit emotional and social concerns about facial appearance that are higher than the general population. Many are undergoing midlife situational stresses and may lack the positive characteristics to deal with them. The most common diagnoses seen include depression, impulsivity, unstable personality, and passive dependence, albeit not necessarily serious. Improvement in body image is the major driver for surgery. Characteristics of female patients as defined by their age are described. These include the younger emotionally dependent group, the worker group of middle age, and the older grief group. Male patients are seen to have a higher level of psychological dysfunction, but a higher improvement in postoperative quality of life. Motivations for surgery include increasing self-esteem, making new friends, improving relationships, and getting better jobs. Overall patient satisfaction is more than 95%, with improvement seen in positive changes in their life, increased self-confidence and self-esteem, decreased self-consciousness about their appearance, and overall improvement in quality of life. Postoperative psychological reactions are seen in about half the patients, these primarily being anxiety and depression of varying degrees. Predictors of patient satisfaction include the desire for self-image improvement in contradistinction to a change in life situation. Negative predictors include male sex, young age, unrealistic expectations, relationship disturbances, and preexisting psychological pathology. The importance of good patient selection in achieving a satisfied patient is outlined and emphasized.
Keywords: psychology; patient selection; cosmetic surgery; quality-of-life; self-esteem